PENGARUH MACAM MULSA DAN PEMANGKASAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SEMANGKA (Citrullus vulgaris schard). - Imam - Junaedi; Sartono Joko Santosa; Endang Sri Sudalmi (Innofarm:Jurnal Inovasi Pertanian, 2013)
The research "The effect kind of mulch and pruning on the growth and yield of watermelon (Citrullus vulgaris schard). Aimed to known the effect kind of mulching and pruning on the growth and yield of watermelon. Had been done 21th May 2013 to 19th July 2013 Tohudan village, Colomadu district, Karanganyar regency with altitude of 110 meters above sea level. This research arranged by Completely Randomized Block Design (RCBD) with two factors treatments. The first factor is kind of mulch consist of: without the mulch, the reeds mulch, straw mulch, silver black plastic of mulch, and black silver plastic of mulch. The second factor is the effect pruning consists of: without the pruning and with pruning so the obtained ten combined treatment and three replication. The results showed, (1) Treatment kinds of mulch increase Length of Plant, weigh of fruits, circle of fruits, fresh weight of biomass, and dry weight of biomass (2) The best results are treatments silver black plastic of mulch with a length of plant 353,98 cm, and weight of fruit 5.47 kg. (3) Treatment without pruning give results of length of plant the highest 319, 84 cm. (4) The interaction between the kinds of mulch with pruning had no effect at all parameters.   Key words : mulch, pruning, watermelon